2010
DOI: 10.1007/s12253-009-9243-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Corticosteroids on Serum Cystatin C in Thrombocytopenic Purpura and Leukemia

Abstract: The aim of our study was to evaluate the influence of steroid therapy on serum cystatin C (cysC) concentrations in patients with acute lymphoblastic leukemia (ALL) and idiopthiás thrombocytopenias purpura (ITP). We studied 17 patients with ITP (girls: boys =5:12, mean age: 7.6 yrs, range between 1 to 17 years) and 18 patients with ALL (girls: boys =6:12, mean age: 6.3 yrs, range between 2 to 17 years). CysC and white blood cell count (WBC) in both group of patients were determined before and after 300 mg/m(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
6
1
1
Order By: Relevance
“…Some have reported that cystatin C is disproportionally increased in patients with active malignancy [37,38], whereas others have failed to demonstrate this association [33]. Similar controversies exist regarding the independent effect of steroid therapy and the WBC count on cystatin C levels [24,39,40]. We were unable to find an association between the WBC count and cystatin C in our cohort.…”
Section: Discussioncontrasting
confidence: 70%
“…Some have reported that cystatin C is disproportionally increased in patients with active malignancy [37,38], whereas others have failed to demonstrate this association [33]. Similar controversies exist regarding the independent effect of steroid therapy and the WBC count on cystatin C levels [24,39,40]. We were unable to find an association between the WBC count and cystatin C in our cohort.…”
Section: Discussioncontrasting
confidence: 70%
“…This may result in a falsely increased incidence of AKI if assessed by CysC-based eGFR. In contrast, there is controversy over whether glucocorticoids aff ect serum CysC levels in pediatric patients (Bokenkamp et al 2002;Foster et al 2006;Bokenkamp et al 2007;Bardi et al 2010;Slort et al 2012). Therefore, in the present study, the incidence of AKI was compared separately by glucocorticoid therapy status.…”
Section: Discussionmentioning
confidence: 90%
“…Since glucocorticoids may affect serum CysC levels (Bardi et al 2010;Nakamura et al 2018;Cimerman et al 2000), the incidence of AKI based on CysC-based eGFR was compared by glucocorticoid therapy status. No significant differences were found in the incidence of AKI: 77.4% during chemotherapy with glucocorticoids and 77.3% during chemotherapy without glucocorticoids.…”
Section: Incidence Rate and Severity Of Akimentioning
confidence: 99%
“…CysC usually peaks 2-3 days after steroid administration and the effect diminishes by 7 days. Findings in children have been more conflicting, with some studies finding no or limited changes in cysC after administration of high-dose short-course steroids or during chronic steroid administration, while others found dose-dependent increases in cysC [83][84][85][86].…”
Section: Corticosteroidsmentioning
confidence: 99%